The uncommon occurrence of two common inherited disorders in a single patient: a mini case series. (3rd September 2018) - Zuazo, Francisca; Dumitrescu, Alina V.
ABSTRACT: Background : Inherited eye disorders are genetically determined conditions that are present from birth and usually manifest early, although some may develop later in life. Despite their low incidence, they are a common etiology of pediatric blindness. The occurrence of more than one such disease in a patient is very rare. Material and Methods : Case series of two unrelated patients with simultaneous Stargardt disease (STGD1) as well as Stickler's Syndrome (SS), both genetically confirmed. Results : Patient 1: 13-year-old girl was referred for unexplained bilateral decreased vision for 6 months. She had a clinical diagnosis of SS, same as her mother. Her visual acuity was 20/200 with high myopia in both eyes. Her fundus showed foveal/perifoveal atrophy, retinal pigment epithelium (RPE) changes and beaded vitreous. Goldman visual fields (GVF) revealed enlarged blind spots with central depression. A macular dystrophy was suspected. Genetic testing revealed SS, COL11A1 gene mutation; and STGD1, ABCA4 gene mutation. Patient 2: 67-year-old female with a history of hearing loss, cleft palate, strabismus and myopia, same as her daughter and granddaughters. Her visual acuity was 20/400 and 20/250 with high myopia in both eyes. Her fundus showed macular pigment clumping and RPE atrophy with no vitreous abnormality. GVF revealed a relative central scotoma with generalized constriction. Genetic testing revealed SS, COL11A2 gene mutation; and STGD1, ABCA4 gene mutation. Conclusions : If a patient's signs/symptoms cannot be explained by the working/known diagnosis, additional work up should be pursued for concomitant diseases. SS and STGD1 are commonly diagnosed inherited eye disorders and can coexist in one patient on rare occasions.